First trimester screening - (:unkn) unknown (My University, 2001)
All women, whatever their age, face a small risk of delivering a baby with a physical and/or mental handicap. In some cases the handicap is due to a chromosomal abnormality such as Down syndrome. The only way to know for sure whether or not the fetus has a chromosomal abnormality is by having an invasive test done, such as chorionic villus sampling (CVS) or amniocentesis. However, these tests carry a risk of miscarriage of about 1% (1). The most recent and accurate way of estimating the risk of the fetus having a chromosomal abnormality is carried out at 11-13 weeks and depends on the: a) age of the mother b) amount of fluid behind the neck of the fetus (nuchal translucency) (Fig. 1) c) presence of any fetal abnormalities d) fetal heart rate e) level of two hormones (β-HCG and PAPP-A)in the mother's blood. After the scan, on the basis of all the above factors, the estimated risk for Down syndrome can be discussed with the patient. Irrespective of whether the patient decides to have an invasive test, it is recommended that she has a scan at 20 weeks to check for physical abnormalities (2).
Keywords: First trimester screening; Nuchal translucency